Pathways to careers in health care - King, Christopher T.; Hong, Philip Young P., 1972- (W.E. Upjohn Institute for Employment Research, 2019)
"The authors in this book present findings, lessons, and recommendations that emanated from HPOG research and evaluations for consideration by policymakers, program operators, and other researchers"--